Dipeptidyl Peptidase-4 Inhibitors as a Third-Line Oral Antihyperglycaemic Agent in Patients with Type 2 Diabetes Mellitus: The Impact of Ethnicity. (10th August 2014) - Zhang, X.; Brooks, B.; Molyneaux, L.; Landy, E.; Banatwalla, R.; Wu, T.; Wong, J.; Su, B.; Yue, D. K.
Abstract : Aims . The aim of this study is to examine the efficacy of adding a dipeptidyl peptidase-4 (DPP-4) inhibitor to patients with type 2 diabetes inadequately controlled by metformin and sulphonylurea combination treatment. The response of Asian and non-Asian patients to this regimen was also examined. Methods . The medical and computerized records of 80 patients were examined. These patients had baseline HbA1c levels ranging from 7.0 to 12.5% and had a DPP-4 inhibitor add-on therapy for a minimum period of 12 weeks. The primary endpoint was the change in HbA1c level before and after DPP-4 inhibitor treatment. Results . During oral triple therapy, there was a reduction of HbA1c from 8.3% (7.7–8.9) to 7.2% (6.8–7.6) and 26 patients (32.5%) achieved an HbA1c <7%. Poor baseline glycaemic control, lower BMI, and younger age were associated with a better response, but duration of diabetes and gender did not affect outcome. The HbA1c reduction was not different between Asians and non-Asians group [−1.00% (0.6–1.3) vs −0.90% (0.4–1.6)]. Conclusions . DPP-4 inhibitor as a third-line add-on therapy can achieve significant glycaemic improvement in patients with type 2 diabetes inadequately controlled on the combination of metformin and sulphonylurea. The improvement in HbA1c was similar between Asian and non-Asian patients.